Letter - Alvaro, Pablo
026-0084-001 "Girton House" Kingsway Hove - Sussex Secretary of Assistance Trades Union Transport House Smith Square London, S.W.1. Hove 2nd June 1939 Dear Sir: We have received the parcel of clothes and had them distributed between the nine socialists fellows who signature the letter. We thank you for the very kind interest you have taken in us. Thanking you once again Yours very sincerely, Pablo Alvaro 292/946/26/84